High-performance artificial nitrogen fixation at ambient conditions using a metal-free electrocatalyst - Qiu, Weibin; Xie, Xiao-Ying; Qiu, Jianding; Fang, Wei-Hai; Liang, Ruping; Ren, Xiang; Ji, Xuqiang; Cui, Guanwei; Asiri, Abdullah M.; Cui, Ganglong; Tang, Bo; Sun, Xuping (Nature communications, 2018)
Conversion of naturally abundant nitrogen to ammonia is a key (bio)chemical process to sustain life and represents a major challenge in chemistry and biology. Electrochemical reduction is emerging as a sustainable strategy for artificial nitrogen fixation at ambient conditions by tackling the hydrogen- and energy-intensive operations of the Haber–Bosch process. However, it is severely challenged by nitrogen activation and requires efficient catalysts for the nitrogen reduction reaction. Here we report that a boron carbide nanosheet acts as a metal-free catalyst for high-performance electrochemical nitrogen-to-ammonia fixation at ambient conditions. The catalyst can achieve a high ammonia yield of 26.57 μg h –1 mg –1 cat. and a fairly high Faradaic efficiency of 15.95% at –0.75 V versus reversible hydrogen electrode, placing it among the most active aqueous-based nitrogen reduction reaction electrocatalysts. Notably, it also shows high electrochemical stability and excellent selectivity. The catalytic mechanism is assessed using density functional theory calculations. Electrochemical reduction of nitrogen is a promising route to industrial-scale nitrogen fixation at ambient conditions, but is challenged by activation of inert nitrogen. Here the authors report a metal-free catalyst that selectively reduces nitrogen to ammonia with high efficiency and stability.